Challenges, strategies, and “lines of flight” in government museums of deterritorialized memories: representation, listening, and community participation as tools for survival (Cadernos de Sociomuseologia, 2026)
When reflecting on social and community museums of deterritorialized memories, the relevance of the communities represented by these institutions being present and active in their actions, discourses, and teams is a passive point. However, when addressing museums managed by the state (federal, state, or municipal), it is essential to consider the power mechanisms in their Foucauldian sense, the tools of co-optation of biopolitics operating in neoliberalism, and the Deleuzian refrain. Therefore, this article argues for the urgency of considering "lines of flight" (Deleuze & Guattari, 1996). to guarantee not only substantive representativeness but also participatory listening and the incorporation of community demands into their programming and management.Keywords: deterritorialized memories; social museums; community museums; substantive representativeness; lines of flight.